Ekonomi Politik Dalam Pengelolaan Wisata Heritage: Studi Kasus Destinasi Wisata Kampung Vietnam (Memorial of Galang) di Kota Batam - Okta, Auliana; Tumanggor, Ingnasia Santa Lovian Br (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Tourism is one of the important industries in the development of the Indonesian economy, especially through cultural heritage tourism that focuses on cultural and historical heritage. This study examines the political economy in the management of heritage tourism in Kampung Vietnam (Memorial of Galang) in Batam City, which is the site of a former Vietnamese refugee camp. Using a qualitative approach and literature study, this study explores the dynamics of management involving the government, local communities, and investors. Although Kampung Vietnam has great potential, challenges such as minimal infrastructure, ineffective promotion, and low community involvement hinder its development. This study suggests the need for infrastructure revitalization, increased promotion, and active community involvement to create a sustainable and inclusive tourism destination.